Patient heterogeneity in dose-finding trials - part 1: methods for 2 groups - Conaway, Mark (Henry Stewart Talks, 2018)
Review of traditional dose-finding designs, 2-group dose-finding trials, 2-sample CRM, Shift model, Matrix order, Hwang-Peddada estimation